Prostate-Specific Antigen Levels Among Diabetic Men: Exploring Patients Attending Outpatient Clinic in Yemen - Al-abd, Nazeh; Alshakka, Mohammed; Mohamed Ibrahim, Mohamed Izham (Archives of Men's Health, 2020)
Introduction: It has been reported that patients with diabetes have a decreased risk for developing prostate cancer. The study aimed to measure Prostate-specific antigen (PSA) levels among diabetic men who had not previously been diagnosed with prostate cancer. Materials and Methods: A cross-sectional study was carried out in public hospitals among diabetic men in Aden, Yemen. A predesigned structured questionnaire, including the personal data as well as physical and clinical characteristics of the study population, such as height, weight, smoking status, the duration of diabetes, and the type of treatment, was included. Blood samples were collected from the respondents, and the levels of fasting blood glucose (FBG) and PSA were measured. The data were analyzed using descriptive and inferential statistics. Results: A total of 145 diabetic male patients were included in this study. The mean PSA level of the respondents was 2.56 ng/ml. There were significant differences in PSA levels according to patient age (p=0.000). The elderly patients exhibited significantly higher PSA levels than the younger groups. The PSA levels of smokers (2.60±0.48 ng/ml) were significantly higher (p=0.035) than those of nonsmokers (2.45±0.65 ng/ml). However, no significant difference was found in PSA levels according to body mass index (BMI) category, the type of treatment, or the duration of diabetes. Additionally, our results showed that PSA levels were not significantly correlated with FBG levels. Conclusion: PSA levels were associated with age and smoking status, but not with BMI, the type of diabetic treatment, the duration of diabetes, or with FBG levels.